2020
DOI: 10.1021/acsami.0c18916
|View full text |Cite
|
Sign up to set email alerts
|

Tough Underwater Super-tape Composed of Semi-interpenetrating Polymer Networks with a Water-Repelling Liquid Surface

Abstract: Despite recent advances in bioinspired underwater adhesives, achieving tough, fast, and stable adhesion in aqueous environments is still challenging. Here, an underwater super-tape with semi-interpenetrating polymer networks (SIPNs) and a water-repelling liquid surface is synthesized. In the SIPN, the linear chains easily diffuse to adapt to the adherends, and the cross-linked chains provide the super-tape with high dimensional stability. Meanwhile, both the linear and cross-linked chains bear many catechol gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…For example, Liu et al found that the application of a small amount of hydrophobic solvent (e.g., chloroform and methyl benzoate) on the surface of a catechol-based elastomer (≈0.3 mg cm -2 ) increased the underwater adhesion strength of the material (≈0.9 MPa). [24] It was demonstrated that the hydrophobic solvent absorbed on the surface of the tape can soften the polymers and repel the hydration layer on the adherend, thereby enabling their close contact to form strong interactions (Figure 9a).…”
Section: Adhesives Based On Molecular Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Liu et al found that the application of a small amount of hydrophobic solvent (e.g., chloroform and methyl benzoate) on the surface of a catechol-based elastomer (≈0.3 mg cm -2 ) increased the underwater adhesion strength of the material (≈0.9 MPa). [24] It was demonstrated that the hydrophobic solvent absorbed on the surface of the tape can soften the polymers and repel the hydration layer on the adherend, thereby enabling their close contact to form strong interactions (Figure 9a).…”
Section: Adhesives Based On Molecular Interactionsmentioning
confidence: 99%
“…Reproduced with permission. [ 24 ] Copyright 2020 American Chemical Society. b) Underwater adhesive hydrogels with a hydrophobic surface.…”
Section: Tape‐type Underwater Adhesivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinate noncovalent bonds led to a dynamic reversible network where the moduli of hydrogels were frequency-dependent, which could relax at low frequency and become tensile at the high frequency. [26] As G 10 F 0.05 P 0.1 showed the best anti-deformation feature in stress amplitude sweep mode, a study in alternating stress amplitude sweep mode was carried out to test its self-healing property (Figure 3e). Briefly, 36 Pa (much lower than the intersection of G' and G'' of G 10 F 0.05 P 0.1 in Figure 3a) was chosen as minimum stress to keep hydrogels stay in the linear viscoelastic region and 14 000 Pa (much higher than the intersection of G' and G'' of G 10 F 0.05 P 0.1 in Figure 3a) was chosen as maximum stress to completely destroy the network.…”
Section: Rheological Performancementioning
confidence: 99%
“…This approach has been used to fabricate coating, adhesives, hydrogels, etc. [ 18 , 19 , 20 , 21 ]. However, this self-crosslinking has not been explored to fabricate dual-crosslinking elastomers.…”
Section: Introductionmentioning
confidence: 99%